Faktor Risiko Kejadian Mikosis Superfisialis pada Nelayan di TPI Puger - Muhammad Fauzi Aldi; Candra Bumi; Adistha Eka Noveyani (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2026)
Background: Superficial mycoses are a common global health problem among fishermen, particularly in tropical regions. Factors such as personal hygiene, length of employment, and obesity have been associated with superficial mycoses, while continuous exposure to high-salt seawater in fishermen’s occupational environments has been hypothesized as a potential protective factor. This study aimed to analyze the risk factors for the incidence of superficial mycoses among fishermen at the Puger Fish Auction Place (FAP) in Jember Regency.Methods: This cross‑sectional analytic study included 97 fishermen selected through quota sampling at Puger Primary Healthcare (PHC). Data on personal hygiene and length of employment were collected using validated questionnaires; obesity status was determined by Body Mass Index (BMI); and superficial mycoses were diagnosed by clinical examination. Univariable analysis described the distribution of all variables, and bivariable analysis using the Chi‑square test assessed associations between risk factors and superficial mycoses.Result: The prevalence of superficial mycoses was 10.3% (10/97). There were no statistically significant associations between personal hygiene (prevalence ratio/PR 1.88; 95% CI 0.42–8.33; p=0.494), length of employment (PR 0.88; 95% CI 0.81–0.95; p=0.353), or obesity (PR 0.36; 95% CI 0.10–1.30; p=0.178) and superficial mycoses.Conclusion: In this cross-sectional study, personal hygiene, length of employment, and obesity were not significantly associated with superficial mycoses among fishermen at Puger Primary Health Care. The relatively low prevalence of infection despite high exposure to conventional risk factors suggests that occupational environmental factors may contribute to reduced susceptibility to infection.